Hubungan Tingkat Pendidikan dengan Kejadian Postpartum Blues pada Ibu Postpartum di RSUD Sumbawa - Herni Hasifah; Utari Salmah Nurparisih; Iga Maliga; Ana Lestari (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Postpartum blues or often also called Maternity Blues or Baby Blues is defined as a syndrome of mild side effects that often appears in the first week after delivery and peaks on the third to fifth day and attacks within 14 days after delivery. This study aims to determine the relationship between education level and the incidence of postpartum blues in postpartum mothers. The type of research used is quantitative research using a cross sectional design. The statistical test used is the chi square test. The sample in this study consisted of 95 respondents. Based on the research results, it is known that there is a relationship between the level of maternal knowledge and the incidence of postpartum blues in postpartum mothers (p value 0.002).